Re-assessing the Psychometric Properties of Stress Appraisal Measure in Ghana Using Multidimensional Graded Response Model - Srem-Sai, Medina; Quansah, Frank; Hagan, John Elvis; Ankomah, Francis; Frimpong, James Boadu; Ogum, Prosper Narteh; Schack, Thomas (Frontiers in Psychology, 2022)
Despite the widespread use of stress appraisal measure questionnaire in the sport psychology related literature, the psychometric properties of this survey instrument across different cultures and samples is still not known. This study sought to validate the stress appraisal measure instrument among male football players in the Ghana Premier League using the multidimensional item response theory. The descriptive cross-sectional survey design was adopted to recruit 424 footballers from the 2020/2021 Ghana premier league season using the census approach. The 28-item Stress Appraisal Measure was used to assess six (6) appraisal mechanisms under primary and secondary cognitive appraisals. The ordered polytomous item response theory was used for analyzing the data. The study found that although some items were problematic, the majority of them were found to have good item parameters, effective scale option functioning, and provided adequate empirical information in the measurement of the stress appraisal. This research concluded that the SAM questionnaire has promising applicability among male footballers who participated in the premier league in Ghana. Future researchers are encouraged to re-validate the stress appraisal measure instrument with a different sample to contribute to the understanding of the applicability of the instrument in non-western populations.